The effect of a walking training program at the LIPOXmax point on the body mass index in male type II diabetes in the 40-60 age group. - Bait , Aissa; Hadj aissa, rafik; Bouslah , Nadir (sports creativity, 2025)
The study aims to identify the effect of a training program by walking to the point (lipoxmax) on the BMI of male diabetics (type II), we relied on the experimental approach because of its adequacy with the study, while the study sample was composed of 12 people with type II, which were randomly selected from the study population, We used the pre and post measurement of the training program using an impedancemetry device to measure the body mass index, as well as a equation for calculating the walking rhythm (LIPOXMAX) which varies from one patient to another, Finally, the results of the study showed that walking to the point (LIPOXMAX) positively affects the reduction in the body mass